Avaliação dos efeitos neurocomportamentais induzidos pela urease de Canavalia ensiformis (JBU) em baratas da espécie nauphoeta cinerea (olivier, 1789) - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Ureases are metalloenzymes that hydrolyze urea to ammonia. These compounds are synthesized by many organisms and have been characterized as natural insecticides. The entomotoxic activity of Canavalia ensiformis urease (Jack Bean Urease, JBU) has been demonstrated in different models of insect pests, although its mechanism of action has not yet been fully elucidated. In this regard, the complexity in the demonstration of natural insecticides mechanism of action increases when these compounds interact with the nervous system of insects, altering the behavior. The aim of this study was to demonstrate the activity induced by JBU on the central nervous system of Nauphoeta cinerea cockroaches and its role in the modulation of grooming behavior of these animals. In this work were used adult cockroaches N. cinerea of both sexes kept in insectary (23-26 °C) with water and food ad libitum. The recording of grooming activity was made by observation in an open field circle where the animal had never been in contact before. The counting of time spending grooming (leg and antenna) was made in an isolated room, silently, using a digital timer during 30 minutes. Treatments were made by means of injection at the insect third abdominal portion with a fixed volume of 20 µL using a Hamilton syringe. The results were obtained by counting the total time spending grooming in seconds in 30 minutes. Data were plotted as the time spending grooming in seconds. Control animals, without the injection of any compound, were also accounted. Statistics were applied using the Student "t" test where p <0.05 indicated significance. In control animals, without any treatment, the grooming rate was 60 ± 5s / 30min for leg and 35 ± 8 s / 30min for antennas (n = 30, respectively). When JBU (1.5, 3 and 6 µg/g of animal) was administered there was a dose-dependent alteration in the groomings level. Thus, at the dose of 1.5 µg/g, no significant change of the leg and antenna groomings were observed (n = 30, p> 0.05, respectively). However, when the dose of 3 µg/g was assayed there was an increase of 160 ± 20s on the time of leg grooming (n = 30, p <0.05), with no modulation in the grooming of antenna. At the highest concentration tested there was an increase of 200 ± 10s in the leg grooming (n = 30, p <0.05), with no change in the grooming of antennas. When the octopamine (15μg/g) was administered the value of leg grooming was of 358 ± 40s, with no change in the grooming of antenna. In these set of experiments, the preadministration of phentolamine (0.1μg/g of animal), and subsequent octopamine (15μg/g) injection resulted in the decrease on the time spending grooming to 79 ± 13s/30min (p <0.05 compared to control octopamine, n=30). When phentolamine + JBU were assayed there was a reduction in the leg grooming rates to 56 ± 7s/30min (p <0.05 compared with the control or JBU octopamine, n = 30). When hydroxylamine (20µg/g of animal), a nitric oxide donor or acetylcholine (54 µg/g animal) was assayed, there was no change in groomings rate. The significative alterations induced by both JBU and octopamine in the leg groomings and the subsequent inhibition by phentolamine, indicate that the octopaminergic system is potentially the molecular target for the development of behavioral effects of C. ensiformis urease in cockoaches.
Keywords: Inseticidas naturais; Ureases; Comportamento de grooming; Sistema octopaminérgico; Natural insecticides; Grooming behavior; Octopaminergic system; CNPQ::CIENCIAS BIOLOGICAS